Recurrent calf myositis as revealing manifestation of Crohn disease: a case report - La Rosa, Anna; Meneghel, Alessandra; Giraudo, Chiara; Zucchetta, Pietro; Tirelli, Francesca; Trevisan, Francesca; Calabrese, Fiorella; Zulian, Francesco (Frontiers in Pediatrics, 2025)
Crohn's disease (CD) is a chronic inflammatory bowel disease (IBD) that may present in children with extraintestinal manifestations (EIM). Inflammatory myopathies are rarely described in this context. Herein we describe the case of a teenager with recurrent episodes of calf myositis, also known as “Gastrocnemius Myalgia Syndrome” (GMS), as the only manifestation of CD in a pre-clinical phase. A 15-year-old girl presented three episodes of acute bilateral calf myositis with inability to walk over a period of three years. Each episode was preceded by febrile upper respiratory tract infections, with levels of IgG for Sars-Cov2 compatible with a recent infection. Clinical and laboratory tests showed an acute inflammatory state which, in the first two episodes, spontaneously improved in about 20 days. During the third episode, a whole-body PET-MRI detected hypermetabolism, associated with muscle edema of the posterior compartment of the legs and thickening of the terminal ileum with significant tracer uptake. Intestinal and muscle biopsies confirmed the diagnosis of CD and focal myositis. The patient was treated with corticosteroids and azathioprine with rapid resolution of pain, fever and intestinal inflammation. Our case clearly shows that GMS should be considered among the EIM of pediatric CD and can precede IBD onset by years. Therefore, CD should be ruled out in all pediatric patients presenting with predominant, recurrent calf myositis.